Simulation of the effectiveness of longitudinal rectangular fins on the efficiency of the double pipe heat exchanger - N. F. Timerbaev; A. K. Ali; Omar Abdulhadi Mustafa Almohamed; A. R. Koryakin (Известия высших учебных заведений: Проблемы энергетики)
In this article, a mathematical simulation of a double pipe heat exchanger is carried out, having the longitudinal rectangular fins with the dimension of (2*3*1000) mm, mounted on the outer surface of the inner tube of the heat exchanger. In this paper, the advantage of using of that type of fins and its effect on the effectiveness of the heat exchanger are studied with the help of the computer program. The carried out research allowsmaking the calculation to find the optimum design parameters of heat exchangers. The outer tube diameter is (34.1mm) while the inner tube diameter is (16.05mm). The tubes wall thickness is (1.5mm) and the model length was (1 m). The hot water is flowing through the inner tube in parallel with the cold water that passing the outer tube. The hot and cold water temperature at the inlet is (75°C & 30°C) respectively. The mass flow rate inside the central pipe is (0.1 kg/s) while the annular pipe carrying (0.3 kg/s). In the present work, the program ANSYS Workbench 15.0 was used to find out the results of heat transfer as well as the behavior of liquids inside the heat exchangers.